Pemilihan Lokasi Usaha Terhadap Kesuksesan Usaha - Rini Mutianisa; Rusnandari Retno Cahyani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The research objective is to analyze the effect of business location selection. The type of research used in this research is a type of library research, namely research conducted using literature, both in the form of books, notes, and reports on previous research results using references, where the data sources are taken from google scholar. The approach used in this research is a qualitative approach with domain data analysis, namely the researcher's efforts to obtain an overview of the data to answer the research focus. Business location on the trader's income variable includes a negative correlation and insignificant relationship. This shows that a strategically chosen location is unlikely to generate more income. Factors to consider in choosing a location, although there are several influential factors, are the proximity to the market (consumers). This location can be seen: 1) The business environment, namely regarding the proximity of the business location to other businesses / competitors, proximity to consumers, proximity to suppliers, and proximity to providers of production equipment / equipment. 2) Location costs, namely regarding building rental prices, whether or not there are renovation costs, interest rates, labor costs, and the amount of taxes. Based on the results of the study, several conclusions can be drawn, namely that business location has a significant influence on business location.